2016
DOI: 10.3390/vaccines4040046
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Microenvironment Metabolism: A New Checkpoint for Anti-Tumor Immunity

Abstract: When a T cell infiltrates a tumor, it is subjected to a variety of immunosuppressive and regulatory signals in the microenvironment. However, it is becoming increasingly clear that due to the proliferative and energetically-deregulated nature of tumor cells, T cells also operate at a metabolic disadvantage. The nutrient dearth of the tumor microenvironment (TME) creates “metabolic checkpoints” upon infiltrating T cells, impacting their ability to survive, proliferate and function effectively. In this review, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
84
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(84 citation statements)
references
References 91 publications
0
84
0
Order By: Relevance
“…Even then, the tumor stroma, including cancer associated fibroblasts, myeloid derived suppressor cells, regulatory T-cells, macrophages, and neutrophils, creates a microenvironment that poses significant additional challenges to T-cells. The tumor microenvironment also alters T cell metabolism thereby promoting immunosuppression, representing another potential barrier [60]. Some or all of these issues may have to be addressed to enable the full potential of tumor-specific T-cells to be unleashed.…”
Section: Engineering T-cells To Combat the Immunosuppressive Tumor MImentioning
confidence: 99%
“…Even then, the tumor stroma, including cancer associated fibroblasts, myeloid derived suppressor cells, regulatory T-cells, macrophages, and neutrophils, creates a microenvironment that poses significant additional challenges to T-cells. The tumor microenvironment also alters T cell metabolism thereby promoting immunosuppression, representing another potential barrier [60]. Some or all of these issues may have to be addressed to enable the full potential of tumor-specific T-cells to be unleashed.…”
Section: Engineering T-cells To Combat the Immunosuppressive Tumor MImentioning
confidence: 99%
“…However, in addition to the distinct population of cells that comprise the tumor microenvironment, it is generally appreciated that the tumor microenvironment has a metabolic landscape distinct among tissues, and that this too may serve as a barrier for antitumor immunity (5,6). Tumors have areas of hypoxia and acidosis, depleted essential amino acids like glutamine and arginine, and have a unique lipid profile among tissues (7,8).…”
Section: Introductionmentioning
confidence: 99%
“…Mounting investigations have indicated that abnormal energy metabolism, playing a crucial role in the origination and progression of tumors, including highefficiency aerobic glycolysis, abnormal fatty acid metabolism, and elevated nucleotide synthesis, provides abundant ATP\NADPH for cells rapid unrestricted growth. 10,13,32 Abnormal fatty acid metabolism is principally manifested by enhanced fatty acid synthesis. 33 ACC, FASN, and SCD, key enzymes in fatty acid synthesis, are controlled by the transcription factor SREBP1.…”
Section: Discussionmentioning
confidence: 99%